The influence of chronic obstructive pulmonary disease on the results of in-hospital treatment and long-term outcomes of patients with NSTEMI and STEMI after percutaneous coronary intervention - Żygadło, Agnieszka (2020)
The co-incidence of COPD with ischemic heart disease is estimated at the level of 20-60%. The aim of the study was to determine the incidence of COPD in patients after myocardial infarction; to assess the impact of COPD on treatment outcomes and to determine the incidence of cardiovascular adverse events in patients with COPD after myocardial infarction. 71 patients took part in the study. The incidence of COPD was 18.31%. Patients with obturation were older, NSTEMI was more frequent in this group. A history of COPD risk factors was present. There were more in-hospital complications. During the one-year follow-up they were more often hospitalized due to exacerbation of heart failure. Patients with obturation received beta blockers less often and required the use of diuretics more frequent. The echocardiographic parameters did not differ between the groups except the lower value of E wave velocity of the tricuspid valve. GLS values in both groups were similar. Lower absolute values of GLS correlated with lower right ventricular FAC, lower TAPSE and S' wave velocity, higher E/E’ values of the tricuspid valve and lower E/A values of mitral inflow. Patients with obturation had a shorter distance in the 6 minute walk test, greater intensity of exercise dyspnea, a higher CAT score, worse quality of life assessed using the WHOQoL-BREF questionnaire.
Keywords: COPD; myocardial infarction; GLS